Tropical tropospheric chemistry and climate change - SUBBARAYA, B. H.; LAL, SHAM; NAJA, M. (MAUSAM, 2001)
A systematic programme of monitoring surface ozone and its precursor gases CH4, CO and NOx (NO + NO2) at some selected sites in the Indian region was started under ISRO’s geosphere biosphere programme in 1991. Measurements have been made at Ahmedabad an urban polluted site, Gadanki a rural relatively clean site, Gurusikhar a high altitude site representative of the free troposphere and Trivandrum a coastal (relatively clean) site influenced by marine air. The data has been used to study different features of troposphere chemistry in the tropics. Some of the results from this programme relevant to the climate change problem are presented in this paper.